2004
DOI: 10.1007/s00418-004-0677-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the placenta

Abstract: Pregnancy is a state of oxidative stress arising from increased placental mitochondrial activity and production of reactive oxygen species (ROS), mainly superoxide anion. The placenta also produces other ROS including nitric oxide, carbon monoxide, and peroxynitrite which have pronounced effects on placental function including trophoblast proliferation and differentiation and vascular reactivity. Excessive production of ROS may occur at certain windows in placental development and in pathologic pregnancies, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
517
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 705 publications
(549 citation statements)
references
References 156 publications
(154 reference statements)
24
517
0
8
Order By: Relevance
“…In this regard, there are clinical and experimental evidences that oxidative stress and/or low intake of antioxidant (Klemmensen et al, 2009) is involved in the etiopathogenesis of the most frequent disorders in the gestational period (Hubel, 1999;Myatt and Cui, 2004;Jauniaux et al, 2006). This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, there are clinical and experimental evidences that oxidative stress and/or low intake of antioxidant (Klemmensen et al, 2009) is involved in the etiopathogenesis of the most frequent disorders in the gestational period (Hubel, 1999;Myatt and Cui, 2004;Jauniaux et al, 2006). This study utilized multiparous sow to better comprehend the status of oxidative stress during different stages of reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that pregnancy is a state of oxidative stress, which is characterized by the placental production of reactive oxygen species including superoxide and hydrogen peroxide (Casanueva and Viteri, 2003;Myatt and Cui, 2004;Chen and Scholl, 2005). Excessive free radical production may cause both lipid and protein oxidation and impair normal endothelial cell function (Serdar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…, 2000 Moller, 1996 , 2000Yoshida, 2001, 2000, 2000Hubel, 1996 Barton, 1999 Toescu, 2004E C Chappell, 1999μmol/gCre , 2003Stocker 1987E 24G7 Shimizu, 1988Yamaguchi, 1994Shimoharada, 1998Shimomura, 2002Yamaguchi, 2002, 1997 Brief Psychiatric Rating Scale Hubel CA, McLaughlin KM, et al (1996). Fasting serum triglycerides, free fatty acids, and malondialdehyde are increased in preeclampsia, are positively correlated,…”
Section: ⅰ.緒 言mentioning
confidence: 99%
“…The placenta is another local source of free radicals. It produces nitric oxide (NO), but also, because it's so rich with free radical producing macrophages, it can contribute to the development of oxidative stress [4], [5].…”
mentioning
confidence: 99%